Overcoming and containing bacterial resistance: appropriate antibiotic use in community-acquired RTIs. Issue 4 (July 2006) - Brunton, Stephen
The global spread of antibiotic resistance is driving the need for more thoughtful antibiotic prescribing. This paper reviews the principles of appropriate antibiotic therapy for community-acquired respiratory tract infections. Appropriate therapy options include: prescribing antibiotics only when they are beneficial to the patient; using agents that target the likely pathogens, taking into account local resistance patterns and risk factors for infection by resistant pathogens while not affecting the bowel flora and other nonrespiratory organisms; and using a dosing schedule and treatment duration that optimizes efficacy, tolerability and adherence to treatment.